PARTISIPASI BENGKEL MOTOR KONVENSIONAL DALAM DIGITAL MARKETING DENGAN MENGIMPLEMENTASIKAN DESIGN THINKING - Widiyanto, Aldi; Hidayat, Irwan; Diwani, Meftyane Liz; Hurairah, Rizky Abu; Nurlela, Siti (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2023)
Technological developments have changed the way of interaction in marketing communication strategies from face to face (conventional) to screen to face (internet marketing). Speedia Motor is a traditional motorbike repair shop, which does not utilize social media and digital marketing in this digital era, this is what makes Speedia Motor experience a decline in product/spare part sales and it is not easy to get customers. The problems above are what made us take this case study to help motorbike repair UMKM digitalize their business, in order to follow current trends, in order to increase the number of customers. The method applied in this research uses the design thinking method, as well as conducting observations at workshop locations and conducting interviews with motorbike repair business owners in order to get to the root of the problem. Our aim in this research is to help UMKM owners who lack understanding in using the e-platform. commerce & social media to be able to reach wider customers, and market available products using digital media or the internet. After implementing digital marketing, the results we found were increasing product visibility and shop visitors online. By conducting this research, we hope to provide an understanding about the effectiveness of social media and digital marketing on conventional motorbike repair shop owners